(untitled) (Third Sector Social Economic Review, 2016)
Working hours is an important topic both for employers and employees in all types of organizations. This paper aims to investigate the attitudes of employees towards work time and also flexible working hours in public institutions. Data were collected via questionnaire from employees (N=249) from different occupations such as policemen, teachers or medical doctors. Results show that although there exist statistically significant differences among groups in terms of occupation, most of the employees are in favour of reducing working hours. Nearly half of the employees prefer shorter workweek despite a pay loss. Furthermore, reducing working hours is generally regarded as a factor improving performance by employees. Lastly, most of the employees want to have flexible work time arrangements. The results were discussed within the framework of the relevant literature.